Tree ring variability and climate response of Abies spectabilis along an elevation gradient in Mustang, Nepal - Kharal, D. K.; Meilby, H.; Rayamajhi, S.; Bhuju, D.; Thapa, U. K. (Banko Janakari, 2015)
In mountainous areas including the Himalayas, tree lines are expected to advance to higher altitudes due to global climate change affecting the distribution and growth of plant species. This study aimed at identifying the tree ring variability of Abies spectabilis (D. Don) and its response to the climate along an elevation gradient in the high Himalayas of central Nepal. Tree core samples were collected from four sites in Mustang district. All sites were located in the same valley and exposed to similar weather conditions. Out of 232 samples collected from the sites, Titi lower (2700 m), Titi upper (2900 m), Pangukhark (3100 m) and Lete upper (3300 m), 44, 40, 39 and 41 series were successfully cross-dated and ring-width chronologies including 168, 79, 138 and 156 years previous to 2012 were developed, respectively. Statistically significant differences in average annual radial growth were noted among the four sites with the highest radial growth observed at mid-elevation sites. Chronological statistics based on residual chronologies for the common period revealed that A. spectabilis at the upper elevation site was more climate sensitive than at the other three sites. At the highest-elevation sites the correlation between pre-monsoon precipitation and tree growth was positive, and for the month of May this was statistically significant (p<0.05). Moreover, spring temperature (March-June) was negatively correlated with precipitation and with tree growth at all sites, and at the upper elevation site (3300 m) the correlation was significant for March, April and May. Banko Janakari, Vol. 24, No. 1 pp. 3-13